Young people's motivations to drive: expectations and realities. (January 2018) - Fylan, Fiona; Caveney, Lauren
Highlights: Motivations to drive include independence, personal space, and social and career opportunities. While young people gain independence from driving, other benefits are often not realised. Many assume employers expect them to have a driving licence. Access to reliable and convenient public transport often removes the desire to drive. In their 20s many non-drivers have achieved the benefits driving brings so have less desire to learn. Abstract: Fewer young adults are choosing to learn to drive and there is a safety argument for encouraging those who do learn to delay doing so. In this study we explore what motivates young people to learn to drive and we uncover their expectations – and the reality – of the difference driving makes to their short- and longer-term futures. We conducted 12 focus groups with 48 young people age 16–24. The discussions explored why they do or don't want to drive, the immediate life changes that driving brings as well as how driving might affect their life in the future. We analysed the data using thematic analysis using the question: what motivates young people to learn to drive? We identified five motivations in the data, organised into two themes. The first theme relates to the benefits of maturity. Young people believe driving providesindependence and represents the first stage of becoming an adult. Most rely on their parents for lifts, and therefore parents control and scrutinise their social life. The car as a form ofpersonal space was very important for young people, as they have complete control over this environment, which can be missing in other aspects of their lives. Driving also bestowskudos, particularly for those amongst the first in their peer group to pass their test. Novice drivers enjoy being able to offer lifts to friends and family, although described how this rapidly becomes an imposition. The second theme is about broadening horizons. Young people believe that drivingexpands their social world, enabling them to travel further afield with their friends for day trips because driving is faster, more convenient and cheaper than public transport. In practice, few of those who drive had used their car in this way, instead using it mainly for commuting and getting fast food. Participants talked about how driving opens upcareer opportunities, allowing them to travel to more distant cities for work and study. However, driving usually made accessing work and study opportunities more convenient rather than possible. Instead, the main benefit young people actually experienced was having more time to sleep in the morning. The qualitative nature of the study, together with the inclusion of pre-drivers, drivers and non-drivers, has provided insight into motivations for learning to drive and how the reality of driving often does not match expectations. The results could be used to inform the potential content of an intervention to encourage young people to delay learning to drive.